STUDY OF SOIL IMPROVEMENT OF LAND RECLAMATION USING DREDGED MUD AS THE FILL MATERIAL - Bratanata, Jonathan
Land reclamation will become more challenging in the future due the depleting availability and rising cost of granular fill materials. One solution is to use dredged mud from a nearby riverbed or from the surrounding seabed. The main goal of this final project is to analyze the effectiveness of using dredged mud as the main fill material in land reclamation. Because the dredged mud used mainly consist of soft clay and has a high water content, it has a relatively low bearing capacity and high compressibility level. That is why soil improvement must be carried out. The soil improvement methods explored in this study are prefabricated vertical drain (PVD) with vacuum preloading, cement mixed dredged mud, and rigid inclusion. Each method was analyzed based on their individual specifications and characteristics so that the output is a design recommendation for each method. Based on each design recommendation, a cost analysis has been conducted for each method of soil improvement. The output of that analysis has been compared with the conventional method of land reclamation which uses granular fill with the base soil being treated with PVD and preloading. The results of these analysis are that the PVD with vacuum preloading method is the most efficient method based on the method of construction and cost. Using the recommended designs, the cement treated dredged mud and rigid inclusion methods have a similar cost to the conventional method of reclamation while having a more complex method of construction. However, as the process is refined and optimized for both the cement treated dredged mud and rigid inclusion methods, then both methods can be a viable alternative for land reclamation using dredged mud as the fill material.